The estimation of the pore space structure of rock-reservoir by the petrophisycal and logging data - VYZHVA, S.; BEZRODNA, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Pore space structure of the carbonate reservoirs (Machuska area, oil well №1) filtration properties are determined by the petrophysical and well-logging data.